Glutamate Receptor-Mediated Oligodendrocyte Toxicity in Periventricular Leukomalacia: A Protective Role for Topiramate - Follett, Pamela L. (J Neurosci, 2004)
Periventricular leukomalacia is a form of hypoxic–ischemic cerebral white matter injury seen most commonly in premature infants and is the major antecedent of cerebral palsy. Glutamate receptor-mediated excitotoxicity is a predominant mechanism of hypoxic–ischemic injury to developing cerebral white matter. We have demonstrated previously the protective effect of AMPA–kainate-type glutamate receptor blockade in a rodent model of periventricular leukomalacia. The present study explores the therapeutic potential of glutamate receptor blockade for hypoxic–ischemic white matter injury. We demonstrate that AMPA receptors are expressed on developing human oligodendrocytes that populate fetal white matter at 23–32 weeks gestation, the period of highest risk for periventricular leukomalacia. We show that the clinically available anticonvulsant topiramate, when administered post-insult in vivo, is protective against selective hypoxic–ischemic white matter injury and decreases the subsequent neuromotor deficits. We further demonstrate that topiramate attenuates AMPA–kainate receptor-mediated cell death and calcium influx, as well as kainate-evoked currents in developing oligodendrocytes, similar to the AMPA–kainate receptor antagonist 6-nitro-7-sulfamoylbenzo-(f)quinoxaline-2,3-dione (NBQX). Notably, protective doses of NBQX and topiramate do not affect normal maturation and proliferation of oligodendrocytes either in vivo or in vitro. Taken together, these results suggest that AMPA–kainate receptor blockade may have potential for translation as a therapeutic strategy for periventricular leukomalacia and that the mechanism of protective efficacy of topiramate is caused at least in part by attenuation of excitotoxic injury to premyelinating oligodendrocytes in developing white matter.